The fine structure of ependymomas. (January 2014) - Baloyannis, Stavros J; Baloyannis, Ioannis S
SUMMARY Electron microscopy is a useful diagnostic technique in order to confirm or establish a definitive diagnosis in brain tumors that may have an atypical histological pattern, which requires a concrete diagnosis. In ependymomas, electron microscopy reveals morphological characters that have a pathognomonic diagnostic value, therefore allowing a definitive diagnosis. The main fine structural criteria of ependymomas consist of the numerous microvilli and cilia, which are incorporated in the cell body or extended freely in the intracellular space; the centriole or blepharoplast, which is located in the basis of the cilia; the large number of the fragmented microtubules in the perikaryon and the cellular processes (any small cellular projection into the neutrophil or intracellular space); the junctional apparatus between the cells, such as zonula adherens, zonula occludens and puncta adherentia; the basement membrane-like structure, seen in papillary ependymomas and ependymomas of the filum terminale; and the elongated cells in the loose intracellular space, commonly seen in myxopapillary ependymomas.